2020
DOI: 10.21037/atm.2020.04.38
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of expression differences of immune genes in non-small cell lung cancer based on TCGA and ImmPort data sets and the application of a prognostic model

Abstract: Background: There has been little investigation carried out into the activity of immune-related genes in the prognosis of non-small cell lung cancer (NSCLC). Our study set out to analyze the correlation between the differential expression of immune genes and NSCLC prognosis by screening the differential expression of immune genes. Based on the immune genes identified, we aimed to construct a prognostic risk model and explore some novel molecules which have predictive potential for therapeutic effect and progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Although surgery and some replacement therapies including immunotherapy have been widely applied for pRCC patients, the limited response rate and unsatisfied outcomes motivated us to further explore the more appropriate methods to improve the therapeutic efficiency and achieve more personalized treatment from the perspective of predicting prognosis [ 21 23 ]. Because of the significantly individual variation, a class of genetic markers including coding and non-coding genes attracted increasing attentions in the past few years [ 24 26 ]. Liu et al indicated lncRNA KTN1-AS1 played the remarkable roles on predicting the poor prognosis of non-small cell lung cancer and facilitate tumor progression through regulating miR-23b/DEPDC1 axis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although surgery and some replacement therapies including immunotherapy have been widely applied for pRCC patients, the limited response rate and unsatisfied outcomes motivated us to further explore the more appropriate methods to improve the therapeutic efficiency and achieve more personalized treatment from the perspective of predicting prognosis [ 21 23 ]. Because of the significantly individual variation, a class of genetic markers including coding and non-coding genes attracted increasing attentions in the past few years [ 24 26 ]. Liu et al indicated lncRNA KTN1-AS1 played the remarkable roles on predicting the poor prognosis of non-small cell lung cancer and facilitate tumor progression through regulating miR-23b/DEPDC1 axis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overlaps represented the numbers of genes predicted by more than one database (a miR-34a-5p; b miR-410-3p; c miR-6720-3p) efficiency and achieve more personalized treatment from the perspective of predicting prognosis[21][22][23]. Because of the significantly individual variation, a class of genetic markers including coding and non-coding genes attracted increasing attentions in the past few years[24][25][26]. Liu et al indicated lncRNA KTN1-AS1 played the remarkable roles on predicting the poor prognosis of non-small cell lung cancer and facilitate tumor progression through regulating miR-23b/DEPDC1 axis[27].…”
mentioning
confidence: 99%
“…Notably, the prediction of tumor prognosis by single mRNA is limited, so it is of great significance to construct comprehensive predict model. For example, the risk model based on systematic immune-related genes shows a superior prognostic values in non-small cell lung cancer [37] . In our work, we constructed a riskscore model according to glycolysis-related mRNAs in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Brie y, genes were recognized as protein-coding genes or non-coding genes based on their Ensembl IDs or Refseq IDs, and only the long non-coding genes in NetAffx Annotation les were retained. We downloaded the immune gene data from the ImmPort data project, and 2,483 immune-associated genes were gained [20,21]. We employed the Pearson correlation to analyze the correlation between immunerelated genes and lncRNAs.…”
Section: Immune-related Lncrnasmentioning
confidence: 99%